ANALISIS SISTEM PELAYANAN KEPEGAWAIAN: (Studi Kasus di Kantor Regional VI BKN Medan) - Syaputra, Andryan; Aslami, Nuri (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
Financial technology innovation in the form of digital wallets is very much in the eyes of the public. The efficiency offered by this payment system has made people start to switch from conventional payments to digital payments. In addition, there are many other factors that influence multi-generations to use digital wallets as an alternative to their daily payments. The use of digital wallets is currently widely applied for online transportation transactions, purchases in e-commerce, to food and beverage delivery services. The method used in this study is a literature study method with the aim of determining the development of the use of digital wallets in the community from various journals sourced from Scopus and several websites that have been analyzed and diodio researchers into a literature review study. From the results obtained, it can be concluded that from year to year there is an increase in the number of digital wallet users, especially in Indonesia. Especially after the Covid-19 pandemic, the number of digital wallet users is increasing because people have to avoid physical contact so that more transactions are made digitally.